2005
DOI: 10.1081/css-200043279
|View full text |Cite
|
Sign up to set email alerts
|

Fe, Cu, Mn, And Zn Input and Availability in Calcareous Soils Amended with the Solid Phase of Pig Slurry

Abstract: A number of feed additives, such as As, Co, Cu, Fe, Mn, Zn, and Se are added to enhance pig growth and performance, but most of these micronutrients pass directly through the animal, which leads to elevated levels in the manure. An accumulation of P and trace elements, especially Zn and Cu, typically occurs with repeated swine manure application on soil. The potential environmental hazard associated with the loading of these elements in amended soils could actually be a positive fact in calcareous soils that u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
3
8
0
3
Order By: Relevance
“…Similar Zn values were found in other winery wastes . In general, micronutrient content obtained in all grape pomace samples that were analyzed in this work were lower than those found in other organic fertilizers used for agricultural soils, as well as in domestic sewage sludges and other animal manures …”
Section: Resultssupporting
confidence: 81%
“…Similar Zn values were found in other winery wastes . In general, micronutrient content obtained in all grape pomace samples that were analyzed in this work were lower than those found in other organic fertilizers used for agricultural soils, as well as in domestic sewage sludges and other animal manures …”
Section: Resultssupporting
confidence: 81%
“…Soil management practices, such as fertilization and amendments, are commonly employed to enhance the nutrient supply and increase crop yields. Nonetheless, the status and behavior of nutrients in soil are difficult to predict (Moral et al, 2002;Moreno-Caselles et al, 2005;2096 R. Ye et al Herencia et al, 2008). Interactions among nutrients affect their availability to crops as an over-abundance of one nutrient may lead to a deficiency of another.…”
Section: Introductionmentioning
confidence: 99%
“…In amended soils, Cu was present mostly in the organic matter fraction (Lai and Cheung 1999;Han et al 2000). In addition, Moreno-Caselles et al (2005) observed a strong correlation between the DTPA-extractable Cu fraction and the organic matter content in amended soils.…”
Section: Micronutrient Concentrationmentioning
confidence: 86%
“…(2001) observed that the extractable Fe in swine manure -amended soils increased to a lesser degree than Mn and Zn. Moreno-Caselles et al (2005) observed that Fe in SPPSamended soils seemed to be in non-readily available forms after application. For Milan cabbage, the organic treatments based on the SPPS decreased the Fe concentration in the commercial part compared to control plants.…”
Section: Micronutrient Concentrationmentioning
confidence: 95%